2017
DOI: 10.1111/hdi.12532
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers upon discontinuation of renal replacement therapy predict 60‐day survival and renal recovery in critically ill patients with acute kidney injury

Abstract: Introduction: There is no consensus on the specific indications for weaning critically ill patients with acute kidney injury (AKI) off renal replacement therapy (RRT). This study aimed to explore the prognostic value of several biomarkers measured upon discontinuation of RRT for their value in predicting 60-day survival and renal recovery in an effort to add knowledge to the decision-making process regarding RRT withdrawal. Methods:We prospectively enrolled 102 patients with AKI who required RRT from the inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…Similarly, a recent study also found that serum CysC, measured when RRT was discontinued, showed the largest AUC value for predicting 60-day renal recovery. In this study, recovery was defined as a serum creatinine level not exceeding 0.5 mg/dL above the baseline value, in patients with AKI who required RRT in the ICU [10]. These results could be supported by the evidence that levels of CysC are less likely to be influenced by continuous venovenous hemodiafiltration or hemofiltration, compared with serum NGAL or creatinine [21][22][23].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Similarly, a recent study also found that serum CysC, measured when RRT was discontinued, showed the largest AUC value for predicting 60-day renal recovery. In this study, recovery was defined as a serum creatinine level not exceeding 0.5 mg/dL above the baseline value, in patients with AKI who required RRT in the ICU [10]. These results could be supported by the evidence that levels of CysC are less likely to be influenced by continuous venovenous hemodiafiltration or hemofiltration, compared with serum NGAL or creatinine [21][22][23].…”
Section: Discussionmentioning
confidence: 74%
“…However, urine output at the time of cessation was reported as the most important predictor of the successful weaning of RRT [7][8][9][10]26], and many studies adapted the criteria for discontinue RRT based on the urine output exceeded 400−500ml/day [4,5,27]. Uchino et al found that a urine output of > 400 ml/day, without diuretics at CRRT cessation, had the greatest AUC value of 0.845, but diuretics negatively affected the predictive ability of urine output [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The predictive effect of NGAL was not further analyzed in the different groups. Additionally, another study assessed the prognostic value of several biomarkers measured upon the discontinuation of RRT for their value in predicting 60-day survival and renal recovery; the study reported that serum CysC (AUROC 0.743, p = 0.002) and urine output (AUROC 0.743, p = 0.002) were better predictors of 60-day renal recovery than serum creatinine (AUROC 0.691, p = 0.015) and NGAL (AUROC 0.661, p = 0.04) [23]. Renal recovery was defined as a serum creatinine level no higher than 0.5 mg/dL above the baseline value.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%